Naturalistyczny i antynaturalistyczny model teorii prawa: [Naturalistic and antinaturalistic model of thery of law] (Studia Prawnicze / The Legal Studies, 1984)
The article attempts to give most general characteristics of two relatively contrasting theoretical models of theory of law - naturalistic and anti-naturalistic ones. The basis of distinguishing naturalistic strategy from anti-naturalistic one in social sciences is the fact of having accepted methods of physics (strictly empirical procedures) in research in the field of jurisprudence. The existence of naturalistic trend in the history of development of science is connected with positivistic philosophy and the existence of anti-naturalistic trend - with antipositivistic philosophy of life and Neo-Kantianism.In theory of law the following theoretical and legal schools had naturalistic character: Scandinavian, psychological, legal realism, sociological jurisprudence and Marxist ones. A theoretical model of naturalistic jurisprudence may have two variants which have been presented here. The first one, strictly empirical, where jurisprudence is empirical natural science, the second one — a more general variant of the model where jurisprudence is empirical science in a wide meaning of the word.Four theoretical and legal schools: normativivistic, of philosopsy of culture, phenomenologic and existentialistic are considered anti-naturalistic schools. A theoretical model here has also two variants. A detailed one assumes full contrast between theory o law and empirical sciences - about facts. A more general one stresses special features of jurisprudence Which allow to distinguish the science from natural sciences (empirical - do the traditional meaning of the word).Only moderate variants of those Models may be reialized in practice. The analysis of those models enables to consider the problems of law and methods of examining it from the point of view which occurs rather rarely in the modern theory of law.